Clinical and Epidemiological Aspects of The Course of Urolithiasis and Its Treatment Among the Population of the Kabardino-Balkarian Republic - R. M. Aramisova; L. T. Khokonova; Z. A. Kambachokova; L. M. Taukenova; A. R. Shogenova; D. S. Gogaeva; E. Kh. Dadarova; K. Kh. Temmoeva; A. Zh. Kholaeva; L. Z. Khatsukova; I. M. Khagieva (Антибиотики и Химиотерапия)
Urolithiasis (UL) occupies a leading place in the structure of urologic diseases and is characterized by an increase in morbidity, accompanied by serious complications leading to disability and mortality among the working-age population. In order to establish a comprehensive solution to the problem, it is necessary to study the aspects of UL epidemiology in each region for early diagnosis and timely treatment. Based on the study of statistical materials, the specifics of UL spread in the Kabardino-Balkarian Republic are shown.